Kesenian Masukkiri sebagai Media Integrasi Sosial dan Nilai Keislaman Komunitas Bugis Pagatan - Nurhadi, Ahmad; Budhi, Setia (Prodi Sosiologi FISIP ULM, 2025)
Amid the challenges of modernization and declining interest among younger generations in local traditions, the traditional art of masukkiri, a combination of Maulid Al-Barzanji recitation and the unique rebana percussion of the Bugis Pagatan community in Pakatellu Village, continues to be preserved as an important Islamic and cultural heritage. This study analyzes the social functions of masukkiri in promoting social integration, reinforcing religious values, and sustaining the community’s collective identity. Employing a descriptive qualitative method, the research is framed by Structural Functionalism and Talcott Parsons’ AGIL scheme. Data were gathered through non-participant observation, semi-structured interviews with traditional leaders, performers, and community members, as well as documentation. Analysis was conducted using Miles and Huberman’s interactive model. The findings indicate that Masukkiri serves as an integrative platform that bridges generations and social groups through shared spiritual and social experiences. It functions as a medium for transmitting religious and moral values and for cultural socialization across generations. Through the performance of Maulid Al-Barzanji accompanied by rebana in religious and traditional events, Masukkiri strengthens social cohesion and helps preserve local cultural identity. This study contributes to the sociological discourse on how traditional arts function as adaptive and dynamic systems that maintain community structure amidst changing social contexts. The preservation of masukkiri is recommended through community-based cultural education, collaboration among stakeholders, supportive policy, and digital media engagement to attract younger audiences.